How to meet requirements for hazardous waste landfill design, construction, and closure - United States. Environmental Protection Agency (Park Ridge, N.J., U.S.A. : Noyes Data Corp., 1990)
Presents a summary of EPA regulations and guidances on the design of double liners and leachate collection and removal systems, leak detection systems, final cover, and construction quality assurance for hazardous waste landfills.
Overview of Minimum Technology Guidance and Regulations for Hazardous Waste Landfills Liner Design: Clay Liners Flexible Membrane Liners Elements of Liquid Management at Waste Containment Sites Securing a Completed Landfill Construction, Quality Assurance, and Control: Construction of Clay Liners Construction of Flexible Membrane Liners Liner Compatibility with Wastes Long-Term Considerations: Problems Areas and Unknowns Leak Response Action Plans
Spine title: How to meet requirements for hazardous waste landfill
Includes bibliographical references
Keywords: Hazardous waste sites -- Standards -- United States